Morphometric and molecular differentiation between quetzal subspecies of Pharomachrus mocinno (Trogoniformes: Trogonidae) - Sofía Solórzano; Ken Oyama (Revista de Biología Tropical, 2010)
The resplendent Quetzal (Pharomachrus mocinno) is an endemic Mesoamerican bird species of conservation concern. Within this species, the subspecies P. m. costaricensis and P. m. mocinno, have been recognized by apparent morphometric differences; however, presently there is no sufficient data for confirmation. We analyzed eight morphometric attributes of the body from 41 quetzals: body length, tarsus and cord wing, as well as the length, wide and depth of the bill, body weight; and in the case of the males, the length of the long upper-tail cover feathers. We used multivariate analyses to discriminate morphometric differences between subspecies and contrasted each morphometric attribute between and within subspecies with paired non-parametric Wilcoxon test. In order to review the intraspecific taxonomic status of this bird, we added phylogenetic analysis, and genetic divergence and differentiation based on nucleotide variations in four sequences of mtDNA. The nucleotide variation was estimated in control region, subunit NDH6, and tRNA Glu and tRNA Phe in 26 quetzals from eight localities distributed in five countries. We estimated the genetic divergence and differentiation between subspecies according to a mutation-drift equilibrium model. We obtained the best mutation nucleotide model following the procedure implemented in model test program. We constructed the phylogenetic relationships between subspecies by maximum parsimony and maximum likelihood using PAUP, as well as with Bayesian statistics. The multivariate analyses showed two different morphometric groups, and individuals clustered according to the subspecies that they belong. The paired comparisons between subspecies showed strong differences in most of the attributes analyzed. Along the four mtDNA sequences, we identified 32 nucleotide positions that have a particular nucleotide according to the quetzals subspecies. The genetic divergence and the differentiation was strong and markedly showed two groups within P. mocinno that corresponded to the quetzals subspecies. The model selected for our data was TVM+G. The three phylogenetic methods here used recovered two clear monophyletic clades corresponding to each subspecies, and evidenced a significant and true partition of P. mocinno species into two different genetic, morphometric and ecologic groups. Additionally, according to our calculations, the gene flow between subspecies is interrupted at least from three million years ago. Thus we propose that P. mocinno be divided in two independent species: P. mocinno (Northern species, from Mexico to Nicaragua) and in P. costaricensis (Southern species, Costa Rica and Panama). This new taxonomic classification of the quetzal subspecies allows us to get well conservation achievements because the evaluation about the kind and magnitude of the threats could be more precise. Rev. Biol. Trop. 58 (1): 357-371. Epub 2010 March 01. El Quetzal (Pharomachrus mocinno) es un ave endémica mesoamericana de interés en conservación. Dentro de esta especie, se reconocen a las subespecies P. m. costaricensis y P. m. mocinno por aparentes diferencias morfométricas, sin embargo, hasta el momento no hay datos suficientes que las confirmen. En este estudio, analizamos ocho rasgos morfométricos de 41 quetzales: la longitud del cuerpo, del tarso y de la cuerda alar, así como la longitud, el ancho y la profundidad del pico, el peso corporal, y en el caso de los machos, la longitud de las plumas cobertoras supracaudales. Usamos análisis multivariados para discriminar diferencias morfométricas entre las subespecies. Comparamos cada rasgo morfométrico dentro y entre las subespecies a partir de comparaciones pareadas con el análisis no-paramétrico de Wilcoxon. Realizamos análisis filogenéticos, y de diferenciación y divergencia genéticas fundamentados en las variaciones nucleotídicas de cuatro secuencias de ADNm con la finalidad de revisar el estatus taxonómico de esta ave. La variación nucleotídica fue estimada en la región control, la subunidad NDH6 y los tRNA Glu y tRNA Phe en 26 quetzales de ocho localidades de cinco países. Estimamos la divergencia y la diferenciación genética entre subespecies con base en el modelo de equilibrio mutación-deriva. Obtuvimos el mejor modelo de mutación nucleotídica siguiendo el procedimiento implementado en el programa Model test. Construimos las relaciones filogenéticas entre las subespecies con máxima parsimonia y máxima verosimilitud usando PAUP, así con estadística Bayesiana. Los análisis multivariados discriminaron dos grupos morfométricos, y los individuos se agruparon de acuerdo con la subespecie a la que pertenecen. Las comparaciones pareadas entre las subespecies mostraron fuertes diferencias en la mayoría de los rasgos analizados. En las cuatro secuencias de ADNmt identificamos 32 posiciones nucleotídicas que tienen un nucleótido particular de acuerdo con la subespecie de quetzal. La divergencia genética y la diferenciación fueron marcadas y mostraron dos grupos dentro de P. mocinno que correspondieron a las subespecies de quetzales. El modelo seleccionado para nuestros datos fue el TVM+G. Los tres métodos filogenéticos usados recuperaron dos clados monofiléticos robustos correspondiendo a cada una de las subespecies. Consideramos que nuestros resultados muestran una significativa y real división de P. mocinno en dos grupos genéticos, morfométricos y ecológicos. Además de acuerdo con nuestras estimaciones, el flujo génico está interrumpido entre las subespecies desde al menos hace tres millones de años. Por ello, proponemos que P. mocinno sea dividido en dos especies independientes: P. mocinno (especie norteña, desde México hasta Nicaragua) y P. costaricensis (especie sureña, Costa Rica y Panamá). Esta nueva clasificación de las subespecies de quetzal permitirá mejores logros en su conservación, dado que la evaluación de la clase y magnitud de las amenazas serán más precisas.